2013
DOI: 10.1007/jhep08(2013)073
|View full text |Cite
|
Sign up to set email alerts
|

Moduli stabilization in a de Sitter compactification model

Abstract: We discuss the moduli stabilization in a de Sitter compactification model obtained coupling D-dimensional gravity to scalar and gauge fields. This class of models is characterized by two moduli: one related to the volume of the internal space, the other to the warp factor. While the volume modulus can be fixed by appropriately tuning the gauge field strength, curvature of the internal space, and cosmological constant, the same mechanism does not work for the warp modulus. In this paper we discuss a stabilizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Similar to the R-region, the stability condition for the vacuum state in the L-region imposes restrictions to the allowed values of the Robin coefficient β. That condition excludes the presence of purely imaginary roots λ = i|λ| for the Equation (16). It can be shown that there are no such modes for a/β < D/2 + ν and there is a single mode for a/β > D/2 + ν.…”
Section: Scalar Fieldmentioning
confidence: 95%
See 1 more Smart Citation
“…Similar to the R-region, the stability condition for the vacuum state in the L-region imposes restrictions to the allowed values of the Robin coefficient β. That condition excludes the presence of purely imaginary roots λ = i|λ| for the Equation (16). It can be shown that there are no such modes for a/β < D/2 + ν and there is a single mode for a/β > D/2 + ν.…”
Section: Scalar Fieldmentioning
confidence: 95%
“…This is the well-known Casimir effect [8][9][10][11]. In braneworld models the Casimir forces acting on the branes may provide a mechanism for stabilization of the brane location (for mechanisms of moduli stabilization in warped geometries, see, e.g., [12][13][14][15][16][17][18] and references therein). In particular, this stabilization is required to prevent the variations of physical constants on the branes.…”
Section: Introductionmentioning
confidence: 99%